Pemberdayaan Sumber Daya Manusia: Transformasi Digital Melalui Strategi Pemasaran Digital Pada UMKM Desa Babakbawo, Dukun, Gresik - Alamudi, Abdul Kadir (JURNAL PENGABDIAN MANAJEMEN, 2025)
MSMEs have a significant role in the Indonesian economy, but still face challenges in the use of digital technology for marketing and business development. This community service aims to analyze the impact of digital marketing socialization on increasing the competitiveness of MSMEs in Babakbawo Village, Dukun District, Gresik Regency. The majority of the population in these villages work as farmers, MSME actors, and migrant workers, but many small businesses have closed due to a lack of adaptation to digitalization. The service methods used include training, mentoring, and evaluation of the use of social media and marketplaces. The results of community service are expected to increase the use of digital marketing to increase brand awareness, market affordability, and the competitiveness of local MSMEs. Therefore, sustainable interventions and support from various parties are needed to ensure the sustainability of the MSME digitalization program.